2013
DOI: 10.1590/s0482-50042013000500010
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidades psiquiátricas em pacientes com lúpus eritematoso sistêmico: uma revisão sistemática dos últimos 10 anos

Abstract: Patients with SLE had a higher suicide risk than the general population. More thorough studies to evaluate the psychological and genetic role, specific and non-specific autoimmune inflammatory mechanisms in mood and anxiety disorders are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Studies from other chronic diseases support our findings. 57 58 Thus it is of importance that ‘scarring changes of skin’, 59 ‘mental illness’ 60 and ‘gastrointestinal disorders’ 61 might also be attributable to lupus and are preventable by an early and optimised lupus therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other chronic diseases support our findings. 57 58 Thus it is of importance that ‘scarring changes of skin’, 59 ‘mental illness’ 60 and ‘gastrointestinal disorders’ 61 might also be attributable to lupus and are preventable by an early and optimised lupus therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These autoantibodies emerged as one of the most widespread and dangerous pathogenic agents in CNS, causing impaired neuronal signaling and brain damages and contributing to the onset of a series of neuropsychiatric disorders (Levite, 2014 ). For example, patients affected by epilepsy and SLE, showed antibodies directed to different types of glutamate receptors, anti AMPA-GluR3B (Ganor et al, 2004 , 2005a , b , c ; Goldberg-Stern et al, 2014 ) and anti NMDA-NR2 (Borchers et al, 2005 ; Asano et al, 2013 ; Fanouriakis et al, 2013 ). From a translational perspective, antibodies against the same glutamate receptors have been shown to favor the onset of behavioral and neurochemical alterations also in preclinical models (see Levite, 2014 for a detailed review).…”
Section: Preclinical Animal Models and Autoimmunitymentioning
confidence: 99%
“…Chronic medical illness and chronic neurological diseases have been associated with depression, anxiety, and emotional distress [40,41,42,43,44,45,46]. Literature has shown that psychopathological comorbidities may worsen the prognosis and quality of life in patients with medical illnesses [47].…”
Section: Discussionmentioning
confidence: 99%
“…Katon et al [40] showed that depression was 2-3 times more frequent in chronic medical diseases. The psycho-oncology literature has shown that more than 30% of cancer patients meet the criteria for a mental condition diagnosis [58,59,60], and in chronic autoimmune diseases, psychiatric conditions and psychological distress are important associated problems [46,47,61,62,63]. Many chronic medical diseases are also associated with higher levels of mental problems [49,64].…”
Section: Discussionmentioning
confidence: 99%